Neuro System Structure for Vehicle Recognition and Count in Floating Bridge Specific Conditions - Beroš, Slobodan; Mladenović, Saša; Matošin, Špiro (Promet - Traffic&Transportation, 2012)
The paper presents the research of the sophisticated vehiclerecognition and count system based on the application of theneural network. The basic elements of neural network andadaptive logic network for object recognition are discussed. Theadaptive logic network solution ability based on simple digitalcircuits as crucial in real-time applications is pointed out. Thesimulation based on the use of reduced high level noise pictureand a tree 2. 7. software have shown excellent results. The consideredand simulated adaptive neural network based systemwith its good recognition and convergence is a useful real-timesolution for vehicle recognition and count in the floating bridgesevere conditions.